2018
DOI: 10.21580/economica.2018.9.2.2806
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spiritual Intelligence and Organizational Citizenship Behavior to Employees Performance: Study at Sharia Banks in Gorontalo Province

Abstract: <p>The employees’ existence as an organizational locomotive need to get attention for management because, it is employees who make the organization perform well. Spiritual intelligence and organizational citizenship behaviour (OCB) are known to have effect for improving employee performance. To see this effect, then research was conducted at Sharia Bank in Gorontalo Province with the aim of analyzing and describing the effect of: spiritual intelligence on OCB, spiritual intelligence on employee performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
1
1
Order By: Relevance
“…A healthy and peaceful work environment significantly influence the job satisfaction of Social Welfare Officers (Asumah, Agyapong, & Owusu, 2019;Gómez García, Alonso Sangregorio, & Lucía Llamazares Sánchez, 2018). On the other side, this study's findings differed from some of the already conducted studies in both the developing and developed world (Krisnanda & Surya, 2019;Muhdar, 2018;Samul, 2020;B. Singla & Kaur, 2019).…”
Section: Hypothesis 3: Relationship With Co-workers Pay and Promotion...contrasting
confidence: 88%
“…A healthy and peaceful work environment significantly influence the job satisfaction of Social Welfare Officers (Asumah, Agyapong, & Owusu, 2019;Gómez García, Alonso Sangregorio, & Lucía Llamazares Sánchez, 2018). On the other side, this study's findings differed from some of the already conducted studies in both the developing and developed world (Krisnanda & Surya, 2019;Muhdar, 2018;Samul, 2020;B. Singla & Kaur, 2019).…”
Section: Hypothesis 3: Relationship With Co-workers Pay and Promotion...contrasting
confidence: 88%
“…Some previous research in the research are Herminingsih (2011), Nadeak (2016, Wispandono (2009), Juniartha et al (2017) andHM (2018) their research shows that obtained significant influenced transformational leadership on organizational culture, organizational culture has a significant impacted toward organizational citizenship behavior, behavior repositions applied by organization strategy such: differentiation, focus strategy and cost reduction meanwhile competency reposition performed by concerning on the input of competency, transformational competencies and the output itself, transformational leadership not significant to organizational citizenship behavior, it showed that the influence of transformational leadership on OCB is indirect mediated by employee trust to leader and job satisfaction and spiritual quotient on organizational citizenship behavior have a positive and significant impacted, spiritual quotient has an important role to determine the level of OCB.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Contoh yang bisa disampaikan dalam hal ini adalah seorang petugas perakitan sepatu akan terambil kesempatan 10 menit waktu produktifnya untuk menghasilkan sepatu rakitan bila dia membimbing rekan baru mengoperasikan alat perakitan sepatu selama 10 menit. Berbagai riset tentang OCB menyatakan bahwa OCB berpengaruh langsung positif terhadap kinerja diantaranya adalah riset Muhdar (Muhdar, 2018) namun peneliti lain hanya menemukan pengaruh tidak langsung OCB terhadap kinerja pegawai tersebut (Basu, Pradhan, & Tewari, 2017) dan menyarankan untuk menyelidiki keberadaan pengaruh langsung OCB terhadap pegawai yang bersangkutan.…”
Section: Hasil Dan Pembahasanunclassified